ELIMINATION THERAPY OF UPPER RESPIRATORY TRACT MUCOUS TISSUES AS A MEAN OF PROPHYLAXIS OF INFUENZA AND OTHER ACUTE VIRAL RESPIRATORY TRACT INFECTIONS IN CHILDREN - T.I. Garaschenko; E.P. Sel'kova; M.V. Garaschenko ("Paediatrician" Publishers LLC, 2006)
The efficacy of aqua Maris as a mean for prophylaxis of influenza and other viral upper respiratory tract infections (Vuri) in children between 6 and 10 years (primary school age). It has established that elimination therapy targeted to reduce viral and bacterial colonization of upper respiratory tract is a promising trend in vuri prophylaxis in large groups of children.Key words: viral upper respiratory tract infection, prophylaxis, children.